Uso de las tecnologías de la información y comunicación (TIC) para la difusión de la oferta turística del Grupo Empresarial Xplora Viajes, año 2021 - Vilela Bravo, Tatiana Julady (2022)
One of the problems currently facing the franchises of the Xplora Viajes Business Group is related to the little use of information and communication technologies for the dissemination of tourist planes on demand. In the present work, an analysis of the performance of each franchise will be carried out at the level of the dissemination of information about the products and services they provide. Investigate the causes that cause the lack of interest in working with these technological tools to publicize the offer and the brand and thus capture the attention of potential customers. To corroborate what was stated in the working hypothesis, research techniques such as observation, interviews and questionnaires were used, through which the respective information was collected for analysis and creation of conclusions. The results obtained suggest that the use of information and communication technologies are very relevant in the relationship between the travel agent and the final customer, without neglecting the influence of other factors such as those related to customer service, quality of service. and the professional capacity of the team, among others. In addition to having information that helps us to carry out marketing strategies in such a way that the dissemination has a great reach. The use of information and communication technologies will also allow us to manage statistical studies related to customer information, thus making it easier for us to reach the final consumer in a more suitable way and grow the customer portfolio.